Cross-cultural studies: China and the world : a festschrift in honor of Professor Zhang Longxi - Qian, Suoqiao; Zhang, Longxi (East Asian comparative literature and culture, 2015)
Cross-cultural studies: China and the world, A festschrift in honor of Professor Zhang Longxi's collects twelve essays by eminent scholars across several disciplines in Chinese and cross-cultural studies to celebrate Zhang Longxi's scholarly achievements. As a leading scholar from post-Cultural Revolution China, Zhang Longxi's academic career has set a milestone in cross-cultural studies between China and the world. With an introduction by Qian Suoqiao, and a prologue by Zhang Longxi himself, the volume features masterly essays by Ronald Egan, Torbjörn Lodén, Haun Saussy, Lothar von Falkenhausen, and Hwa Yol Jung among others, which will make significant contributions to Sinological and cross-cultural studies of themselves on the one hand, and demonstrate Zhang Longxi's friendships and scholarly impact on the other.